Not Moving Clauses: Connectivity in Clausal Arguments. (30th April 2013) - Moulton, Keir
Abstract: Novel reconstruction data is introduced which argues that clauses do not move leftward, thus contributing to a long‐standing debate about sentential subjects and topics (Koster 1978, Alrenga 2005). Although fronted clauses appear to reconstruct for variable‐binding purposes, I offer several arguments that these bound‐variable interpretations are only apparent. First, left‐dislocated CPs do not exhibit the kinds of reconstruction interactions that hold of other moved constituents, as discovered by Lebeaux (1991). Second, we find apparent bound variables in left‐dislocated CPs that can be shown to have no movement source that would provide a site for reconstruction. I will then provide a detailed analysis that marshals the semantics of de re pronouns to explain why covariation without reconstruction is available in these dislocated CPs. Aside from offering a detailed syntax–semantics for clausal complementation, I make the case that there must be syntactic derivations of sentential subjects and topics that do not involve movement and that a parsimonious theory rules out movement of clausal arguments altogether.